2011
DOI: 10.4061/2011/420580
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supraphysiological Doses of Levothyroxine on Sleep in Healthy Subjects: A Prospective Polysomnography Study

Abstract: Disrupted sleep is prevalent in both mood and thyroid disorders. Given the emerging use of thyroid hormones in the treatment of mood disorders, we investigated the effects of supraphysiological doses of levothyroxine (L-T4) on sleep. In an open-label design, 13 healthy subjects received up to 500 μg/day for an eight-week period. A baseline night was polysomnographically recorded (PSG) followed by PSG under the maximum tolerated dose of L-T4. All subjects developed hyperthyroxinemia. The heart rate and respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Limited previous studies showed no difference in sleep quality between hyperthyroid and hypothyroid patients compared with euthyroid subjects (5,6). Our findings regarding subclinical thyroid diseases were consistent with these previous reports.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Limited previous studies showed no difference in sleep quality between hyperthyroid and hypothyroid patients compared with euthyroid subjects (5,6). Our findings regarding subclinical thyroid diseases were consistent with these previous reports.…”
Section: Discussionmentioning
confidence: 80%
“…There are limited data regarding the associations between thyroid hormone abnormalities and sleep disturbance. Kraemer et al (5) studied the effects of hyperthyroxinemia induced by supraphysiologic dosing of levothyroxine (500 µg/day) in 13 healthy subjects for an 8-week period. Sleep architecture evaluated by polysomnography at baseline did not differ from that evaluated while the subjects were hyperthyroxinemic.…”
Section: Introductionmentioning
confidence: 99%
“…Data on possible side effects of such therapies in humans are still inconsistent and vary depending on tissue, organ or function examined. Despite the fact that hyperthyroidism is commonly associated with insomnia, high doses of T4 used for treatment of mood disorders did not cause sleep impairment in otherwise healthy patients (Kraemer et al, 2011). Also, it seems that supraphysiological doses of T4 are not necessarily associated with bone mineral density loss even after a very long period of treatment (Ricken et al, 2012; but see also Chen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Kramer et al [38] observed that the short-term administration of supra-physiologic dosages of L-T4 in healthy subjects did not change sleep architecture. On the other hand, in a recent Chinese study [39] in which PSQI was administered to a large number of subjects, the proportion of poor sleepers was higher in the sub-clinical hypothyroid subjects than the euthyroid subjects.…”
Section: Discussionmentioning
confidence: 99%